Genetic aspects of nonimmune hydrops fetalis - H. A. Sarkisyan; S. V. Dumova; E. I. Shabelnikova; A. A. Fadeeva; K. S. Zizyukina; I. Yu. Zyablova; A. P. Khokhlova; O. I. Savateeva; D. M. Muscherova; I. V. Zhuravleva (Лечащий Врач, 2024)
Background. Nonimmune hydrops fetalis is a heterogeneous disorder characterized by generalized hyperhydration caused by extracellular accumulation of fluid in the tissues and serous cavities of the fetus, in the absence of signs of immune sensitization. The prevalence of nonimmune hydrops fetalis, according to various data, ranges from 0.05 to 0.5%, or about 1:4000 live births. Nonimmune hydrops fetalis is based on more than 150 different nosologies. A significant proportion of all the causes leading to nonimmune hydrops fetalis are disorders in the genetic material of the fetus: chromosomal abnormalities, genetic and genomic disorders, RAS pathologies. Most often, nonimmune hydrops fetalis accompanies mutations with a change in the number of chromosomes, such as Down syndrome, Edwards and Turner. In addition, perinatal viral infections, malformations of the lymphatic, cardiovascular, musculoskeletal and endocrine systems, lysosomal accumulation diseases and other pathologies play an important role in the development of nonimmune hydrops fetalis. The improvement of prenatal diagnostic methods, especially cytogenetic research methods, made it possible to identify the genetic cause of nonimmune hydrops fetalis in a large number of cases, while reducing the group of idiopathic nonimmune hydrops fetalis. Modern ultrasound screening methods make it possible to suspect the presence of a genetic anomaly and associated nonimmune hydrops fetalis already in the first trimester of pregnancy. The identification of the etiology of nonimmune hydrops fetalis, in turn, is a determining factor in choosing the tactics of pregnancy management, determining the possibilities and prospects of intrauterine treatment. Targeted therapy is an effective therapy for genetically determined nonimmune hydrops fetalis, which is a promising direction in the treatment of certain pathologies and is actively developing today. The development of genetically engineered therapy, in addition to correcting the underlying pathology, can lead to a decrease in mortality in nonimmune hydrops fetalis, which currently reaches 90%.Conclusion. This work reflects the etiological structure of nonimmune hydrops fetalis with an emphasis on genetic disorders, and also notes the diagnostic, therapeutic and prognostic features of pregnancy management with nonimmune hydrops fetalis.